Investigation of the proposed solar-driven moisture phenomenon in asphalt shingle roofs. (January 2017) - Boudreaux, Philip; Pallin, Simon; Jackson, Roderick
Unvented attics are an energy-efficiency measure to reduce the thermal load of the conditioned space and decrease the space conditioning energy consumption by about 10%. This retrofit is usually done by spraying polyurethane foam underneath the roof sheathing, and on the gables and soffits of an attic to provide an air barrier and a thermal control layer. Unvented attics perform well from this perspective, but from a moisture perspective sometimes homes with unvented attics have high interior humidity or moisture damage to the roof. As homes become more air tight and energy efficient, a better understanding of the hygrothermal dynamics of homes with energy-efficient envelopes becomes more important. One proposed reason for high unvented attic humidity has been that moisture can come through the asphalt shingle roof system and increase the moisture content of the roof sheathing and attic air. This has been called "solar-driven moisture." Oak Ridge National Laboratory investigated this proposed phenomenon by examining the physical properties of a roof and the physics required for the phenomenon. Results showed that there are not favorable conditions for solar-driven moisture to occur. Oak Ridge National Laboratory also conducted an experimental study in a home with an unvented attic and compared the humidity below the roof sheathing before and after a vapor impermeable underlayment was installed. There was no statistically significant difference in absolute humidity before and after the impermeable underlayment was installed. The outcomes of the theoretical and experimental studies suggest that solar-driven moisture does not occur in any significant amount.